Pelatihan Permainan Tradisional Gobagsodor Dengan Menerapkan Nilai Sosial Budaya Pada Anak SD Citeureup 1 - Taufix Hidayatullah; Idris Supriadi; Devaron Suardi; Rihatul Jannah; Muhammad Purkon; Ahmad Ajiji; Nazwa Nurharistiana (Universitas Maritim AMNI Semarang, 2023)
The rapid development of the times, the revolution has changed many things that must be kept, not to be ignored. Traditional games that are full of cultural and ethnic values, even those that are useful for the best development of children. Modern games that are considered more realistic and even more personal are preferred by children, must be exposed to better motoric and cognitive games. In this study, the theory used is Herbert Spencer's cultural theory which considers that people and culture experience changes at certain stages from simple to complex forms. In addition to the concept of children's motor development according to John Piaget, who has found that games will train children's cognitive abilities better. This research is to see how the existence of traditional games influences the development of children today. This study uses qualitative methods to see how children make traditional games into modern games for children's motoric and cognitive development. As a result, children who do traditional games have much more developed abilities and character. The role of parents and teachers Traditional games that hold meaning and tradition are also important to be preserved. The results of the research itself can be concluded in the game Gobag Sodor there are cultural values that have been applied in the game and there are components of physical conditions that exist in learning at school and in college, such as agility, speed, coordination, strength and balance.